Network Connection BETWEEN TWO COMPUTER USING THE USB CABLE NETWORK / BRIDGE WITH CHIP BRIDGE PL 2501 - Nenny Nenny Anggraini (Majalah SIKOMTEK, 2006)
Network connection is about building a simple network between two computers withoutusing an ethernet card via a USB port. The problem that arises is the USB system is designedonly to communicate with USB devices, so that between the USB Host Controller on acomputer can not directly connect with USB Host Controller on the other computer.By using a USB cable Network / Bridge as a USB device, the USB Host Controller cancommunicate with each other. USB Cable Network / Bridge features an electronic circuit thatfunctions as a regulator of the data traffic from the USB Host Controller on computer A toUSB Host Controller on computer B and vice versa. So in building a network through theUSB port is required equipment as a medium of communication between the USB HostController.